PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN KECAP MANIS ABC (STUDI UD. TOKO HARAPAN BESAR DI DESA SUKA MAJU DK 4D) - -, Nopriani (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
Nopriani. 1225061. 2015. The Effect of Product Attribute forÂ Buying Decision Against ABC Sweet Soy Sauce (A Case Study of Toko Harapan Besar in Desa Suka Maju). Advisor I : Asrori, SPd.MM, and Advisior II : Hidayat SE.MM.Â This study aims to determine whether a product attributes influence on purchase decisions in store Great Hope Village Suka Maju Dk 4D. Variables used in the study is the product attributes (X) and purchasing decisions (Y). The method used to analyze data and research is descriptive analysis and simple regression analysis. The data in though using SPSS produce regression equation Y = 14.546 + From this research, the R2 value of 0.426, this means 42.60%. Product attributes influence on purchase decisions in the store ABC soy sauce great expectations in the village Suka Maju Dk 4D and the rest is contributed by other variables not examined. The conclusion from this study is there is the influence of product attributes on purchase decisions in store Great Hope Village Suka Maju Dk 4D. The advice given by the authors that should pay more attention or mengaevaluasi return strategies that have been made to better match what is expected.